2011
DOI: 10.1002/qj.1869
|View full text |Cite
|
Sign up to set email alerts
|

Expected improvements in the atmospheric humidity profile retrieval using the Megha‐Tropiques microwave payload

Abstract: The microwave payload of the Megha-Tropiques mission is explored to quantify the expected improvements in the retrieval of relative humidity profiles. Estimations of the profiles are performed using a generalized additive model that uses cubic smoothing splines to address the nonlinear dependencies between the brightness temperatures (T B ) in the 183.31 GHz band and the relative humidity of specified tropospheric layers. Under clear-sky and oceanic situations, the six-channel configuration of the SAPHIR radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…Limits of such statistical schemes arise mainly from the training phase performed over a sample of tropical profiles, and from the signature of non-scattering clouds in the scene, as these cannot be accounted for in the radiative transfer computations that are a pre-requisite to the design of the retrieval technique. However, some studies have already shown that the three additional channels of SAPHIR compared to the configuration of the operational 183 GHz radiometers such as AMSU-B or MHS improve the estimation of the relative humidity of the upper part of the troposphere and in its lowest layers (Brogniez et al 2013). …”
Section: Saphir and Megha-tropiquesmentioning
confidence: 99%
“…Limits of such statistical schemes arise mainly from the training phase performed over a sample of tropical profiles, and from the signature of non-scattering clouds in the scene, as these cannot be accounted for in the radiative transfer computations that are a pre-requisite to the design of the retrieval technique. However, some studies have already shown that the three additional channels of SAPHIR compared to the configuration of the operational 183 GHz radiometers such as AMSU-B or MHS improve the estimation of the relative humidity of the upper part of the troposphere and in its lowest layers (Brogniez et al 2013). …”
Section: Saphir and Megha-tropiquesmentioning
confidence: 99%
“…SAPHIR is a cross-track sounder observing the Earth's atmosphere with 6 channels in the 183.31 GHz water vapor strong absorption line. MADRAS is a scanning imager with 9 channels ranging from 18.7 GHz to 157 GHz [2].…”
Section: Satellite Observationsmentioning
confidence: 99%
“…The SAPHIR sounder and the MADRAS imager are both dedicated to improving the documentation of the atmospheric water cycle. In a previous paper, Brogniez et al (2013) showed the expected improvements for the estimation of the RH profiles thanks to the combination of those two instruments, highlighting the gain of information for both ends of the troposphere when only a subset of the channels of MADRAS are combined to SAPHIR measurements. Despite the short lifetime of MADRAS, the availability of a few months of measurements constitutes a test bed for future missions, such as the Second Generation of the Meteorological Operational satellite program (MetOp-SG, EUMETSAT Polar Satellite) planned for launch in 2020.…”
Section: R G Sivira Et Al: Relative Humidity Profiling With Megha-mentioning
confidence: 99%
“…Indeed, as underlined by Brogniez et al (2013), the representation of the cloudy conditions in a training database still presents a limit because reference profiles of cloudy situations with known uncertainties are difficult to gather, which could introduce unwanted additional errors in the methodology. Moreover, we chose to restrict the main part of the current work to a full description of the retrieval models dedicated to oceanic situations.…”
Section: The Radiosonde Profilesmentioning
confidence: 99%
See 1 more Smart Citation